A new validation of the Scholander pressure chamber technique based on stem diameter variations - Cochard, Hervé; Forestier, Sébastien; Améglio, Thierry (Journal of experimental botany, 2001)
The Scholander pressure chamber is one of the most widely used techniques for measuring plant water status. However, the technique has been the subject of recent controversies, and its validity awaits new experimental evidence. This paper presents a new test based on the analysis of the dependence on water potential difference (ΔΨ) of stem diameter variation (ΔD) in walnut (Juglans regia L.). The correlation between ΔΨ and ΔD was established (1) on transpiring potted trees, (2) on dehydrating cut branches, (3) by perfusing the xylem of branch segments with mannitol and sucrose solutions, and (4) by pressurizing segments in a pressure sleeve. The ΔΨ was respectively assessed with a pressure chamber (1, 2), a freezing point osmometer (3) and an air pressure transducer (4). A single relationship was established between ΔΨ (ranging from 0 to −2 MPa) and ΔD for all the experiments. This shows that the measured changes of water potential were correlated to similar modifications of water content in the stems, irrespective of the technique used to induce these changes, and therefore validates the pressure chamber technique and confirms the occurrence of large negative pressures in the xylem of walnut branches.